Battery and liquid injection method thereof, energy storage device and power consumption system
By introducing metal phosphides into the lithium iron phosphate composite material and adding a specific proportion of carbonate substances to the electrolyte, the problems of polarization, capacity loss and gas production expansion of high-power lithium-ion batteries during the cycle process are solved, and the battery cycle energy retention rate and the life of the battery are improved.
Patent Information
- Application Number
- CN202411803172.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-08
AI Technical Summary
High-power lithium-ion batteries are prone to polarization, capacity loss and gas production expansion problems during the cycle, and the cycle life is short. What is difficult to solve is the dissolution of metal phosphides in the electrolyte and catalytic reaction problems.
By introducing metal phosphides into the lithium iron phosphate composite material and adding vinyl carbonate and methyl ethyl carbonate to the electrolyte, the mass ratio is adjusted to improve the conductivity of the positive electrode sheet and reduce the solubility of the metal phosphides.
It effectively reduces the high-power cycling polarization of the battery, improves the cycling energy retention rate of the battery at high power, extends the cycling life of the battery, and solves the dissolution and catalytic reaction problems of metal phosphides in the electrolyte.
Smart Images

Figure BDA0005178781160000121 
Figure BDA0005178781160000131 
Figure BDA0005178781160000132
Abstract
Description
Technical Field
[0001] The present application belongs to the field of energy storage, and specifically relates to a battery and a liquid injection method thereof, an energy storage device and an electricity consumption system. Background Art
[0002] With the continuous development of the lithium-ion battery energy storage market, the new energy storage industry has ushered in a breakthrough in rapid growth. Due to industry demand, higher requirements are placed on the power, life, energy efficiency, safety and other performance of energy storage devices, and 1P high-power energy storage used in the frequency modulation market and portable micro-storage has emerged. However, the chemical system of high-power energy storage devices has a serious irreversible capacity loss and gas expansion due to the high temperature rise caused by the high current value. Its cycle life is shorter than that of conventional 0.25P and 0.5P systems, and the cycle expansion problem is also difficult to solve.
[0003] LiFePO4 has attracted extensive attention as a positive electrode material for lithium-ion batteries because of its abundant raw material reserves, low cost, and strong PO bonding and excellent cycle performance. LiFePO4 has an olivine-type orthorhombic structure, with a space group of Pnma. Its crystal structure includes LiO6 octahedra connected by shared edges and FeO6 octahedra connected by shared corners. This material is a mixed conductor that conducts electricity in both electrons and ions. Since Fe and Fe are not directly connected in the structure, its electronic conductivity is very low, about 10 -9 When Li ions diffuse in the LiFePO4 phase, they are mainly transferred along the (010) direction, so its ion diffusion coefficient is very low, about 10 -16 ~10 -14 cm 2 / s. These shortcomings greatly limit the application of LiFePO4 in the fields of high capacity density and large current discharge. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a battery and its injection method, an energy storage device and an electricity system. The present application can effectively improve the conductivity of the positive electrode plate by introducing metal phosphides into the lithium iron phosphate composite material, thereby effectively reducing the high-power cycle polarization of the battery and improving the cycle energy retention rate of the battery under high power. At the same time, the non-free electrolyte of the present application includes ethylene carbonate and ethyl methyl carbonate, wherein ethylene carbonate has an ultra-high dielectric constant, which can greatly reduce the solubility of metal phosphides in the electrolyte, thereby effectively solving the problem of the reduction reaction of the metal phosphide itself when it is dissolved in the electrolyte after long-term circulation and the catalytic reaction of the electrolyte when it is deposited on the negative electrode.
[0005] In a first aspect, the present application provides a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte includes a free electrolyte and a non-free electrolyte, and the non-free electrolyte includes an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet and an electrolyte in the pores of the separator;
[0006] The non-free electrolyte includes ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the non-free electrolyte is a1, and the mass proportion of ethyl methyl carbonate in the non-free electrolyte is b1;
[0007] The positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a lithium iron phosphate composite material, the lithium iron phosphate composite material includes lithium iron phosphate particles and metal phosphide attached to at least a portion of the surface of the lithium iron phosphate particles, the mass content of the metal phosphide in the lithium iron phosphate composite material is c%, and 0.02c+1≤a1 / b1≤0.22c+1.15 is satisfied.
[0008] According to the battery of the above-mentioned embodiment of the present application, by introducing metal phosphide into the lithium iron phosphate composite material, the conductivity of the positive electrode plate can be effectively improved, thereby effectively reducing the high-power cycle polarization of the battery and improving the cycle energy retention rate of the battery under high power. And its introduction has little effect on the tap density of the lithium iron phosphate material. At the same time, the non-free electrolyte of the present application includes ethylene carbonate and ethyl methyl carbonate, wherein ethylene carbonate has an ultra-high dielectric constant, which can greatly reduce the solubility of metal phosphides (such as ferrous phosphide Fe2P) in the electrolyte, thereby effectively solving the problem of the reduction reaction of the metal phosphide itself when it is dissolved in the electrolyte after long-term circulation and the catalytic reaction of the electrolyte when it is deposited on the negative electrode.
[0009] In addition, the non-free electrolyte is close to the lithium iron phosphate composite material, which is closely related to the dissolution of metal phosphides in the lithium iron phosphate composite material and the formation of repaired SEI film and CEI film. Improving a1 / b1 can effectively inhibit the dissolution of metal phosphides and is conducive to the initial formation of SEI layer and CEI layer with high conductivity and electrochemical stability. The inventors found that the design value of a1 / b1 is sensitive to the change of c. When 0.02c+1≤a1 / b1≤0.22c+1.15 is satisfied, the high-power cycle performance of the battery can be significantly improved. If a1 / b1 is less than 0.02c+1, the positive electrode material will suffer from serious metal phosphide dissolution from the positive electrode into the electrolyte; if a1 / b1 is greater than 0.22c+1.15, the ethylene carbonate enriched in the pores of the positive electrode material will suffer from severe oxidation and decomposition reaction, resulting in the lithium iron phosphate LiFePO4 and the metal phosphide being covered with a large amount of organic products that hinder electron transmission, causing the metal phosphide to be unable to exert its effect. At the same time, the formation of an excessively thick CEI layer also reduces the reversible capacity of LiFePO4.
[0010] In addition, the battery according to the above embodiment of the present application may also have the following additional technical features:
[0011] In some embodiments of the present application, 1<a1 / b1<1.5 is satisfied; and / or, 35%≤a1+b1≤75% is satisfied.
[0012] In some embodiments of the present application, 0.001≤c≤3 is satisfied.
[0013] In some embodiments of the present application, the metal phosphide includes at least one of ferrous phosphide and iron phosphide.
[0014] In some embodiments of the present application, the free-state electrolyte includes ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the free-state electrolyte is a2, and the mass proportion of ethyl methyl carbonate in the free-state electrolyte is b2, satisfying 0.5<a2 / b2<1; and / or, satisfying 35%≤a2+b2≤75%.
[0015] In some embodiments of the present application, a2<a1 is satisfied.
[0016] The second aspect of the present application proposes a liquid injection method for a battery as described in the above embodiment. According to the embodiment of the present application, the liquid injection method includes:
[0017] Use one injection of electrolyte for the first injection, let it stand, and form;
[0018] Use two injections of electrolyte for the second injection, high temperature aging, and volume separation.
[0019] According to the injection method of the embodiment of the present application, the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage are separated by secondary injection, and the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery are flexibly controlled. The dissolution of metal phosphides can be effectively inhibited and it is beneficial to the initial formation of SEI layer and CEI layer with high conductivity and electrochemical stability, thereby achieving the effect of improving the high-power cycle energy retention rate, while also ensuring the high polarity and high electrochemical stability of the electrolyte.
[0020] In addition, the liquid injection method according to the above embodiment of the present application may also have the following additional technical features:
[0021] In some embodiments of the present application, the one injection of electrolyte includes ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the one injection of electrolyte is M1, and the mass proportion of ethyl methyl carbonate in the one injection of electrolyte is N1, satisfying: 1≤M1 / N1≤0.4c+1.7.
[0022] In some embodiments of the present application, 10%≤N1≤M1≤35% is satisfied.
[0023] In some embodiments of the present application, the two electrolytes include ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the two electrolytes is M2, and the mass proportion of ethyl methyl carbonate in the two electrolytes is N2, satisfying: 15%≤M2≤N2≤55%.
[0024] In some embodiments of the present application, a mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2).
[0025] In some embodiments of the present application, the injection coefficient of the sum of the first injection of electrolyte and the second injection of electrolyte is 2.5 g / Ah to 5 g / Ah.
[0026] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the injection method of the above embodiment. As a result, the energy storage device has excellent high-power cycle performance. It should be noted that the features and advantages described above for the battery are also applicable to the energy storage device and will not be repeated here.
[0027] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric equipment. As a result, the electric power system has excellent high-power cycle performance. It should be noted that the above-described features and advantages for the battery are also applicable to the electric power system and will not be repeated here.
[0028] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0029] The embodiments of the present application are described in detail below, which are intended to be used to explain the present application but should not be construed as limiting the present application.
[0030] This application is filed by the inventor based on the following findings:
[0031] In the related art, the methods for improving the kinetic performance of LiFePO4 by modification include: surface carbon coating, reducing particle size, metal ion doping, etc. However, surface carbon coating will significantly reduce the tap density of the material, which is not conducive to improving the volume energy density of the material; metal ion doping will cause vacancies in other positions or block ion channels, which may reduce the theoretical capacity of the material.
[0032] The inventors have found that metal phosphides (such as ferrous phosphide Fe2P) are impurities produced during the calcination process of the traditional solid-phase method for producing LiFePO4. After long-term circulation, they will dissolve in the electrolyte to cause self-discharge, and will deposit at the negative electrode to form iron. The formed iron will continue to catalyze the electrolyte to accelerate the reduction, seriously shortening the cycle life of the battery. Therefore, in actual production, the metal phosphides (such as ferrous phosphide Fe2P) in LiFePO4 need to be treated for impurities.
[0033] At the same time, the inventors also found that metal phosphides (such as ferrous phosphide Fe2P) have good electronic conductivity (conductivity of about 1.5S / cm), and when introduced, they have little effect on the tap density of LiFePO4 materials (for example, the density of ferrous phosphide Fe2P is 6.8g / cm 3 , which is about twice that of LiFePO4), and at a certain content, it can also reduce battery polarization. In addition, the inventors have also found that metal phosphides (such as ferrous phosphide Fe2P) have the effect of improving the low-temperature rate and low-temperature cycle life of the battery. If the metal phosphides in the LiFePO4 material are directly removed by certain technical means, additional costs will be added.
[0034] In view of this, the first aspect of the present application proposes a battery. According to an embodiment of the present application, the battery includes: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the electrolyte includes a free electrolyte and a non-free electrolyte, the non-free electrolyte includes the electrolyte in the pores of the positive electrode sheet, the electrolyte in the pores of the negative electrode sheet and the electrolyte in the pores of the separator, and the rest is a free electrolyte; the non-free electrolyte includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC), and the mass proportion of ethylene carbonate (EC) in the non-free electrolyte is a 1. The mass proportion of ethyl methyl carbonate (EMC) in the non-free electrolyte is b1; the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a lithium iron phosphate composite material, the lithium iron phosphate composite material includes lithium iron phosphate (LiFePO4) particles and metal phosphide attached to at least part of the surface of the lithium iron phosphate particles, the mass content of the metal phosphide in the lithium iron phosphate composite material is c%, and 0.02c+1≤a1 / b1≤0.22c+1.15 is satisfied.
[0035] The principle of the beneficial effect of the battery proposed in this application is described in detail below:
[0036] The present application can effectively improve the conductivity of the positive electrode sheet by introducing metal phosphides into the lithium iron phosphate composite material, thereby effectively reducing the high-power cycle polarization of the battery and improving the cycle energy retention rate of the battery under high power. And its introduction has little effect on the tap density of the lithium iron phosphate material. At the same time, the non-free electrolyte of the present application includes ethylene carbonate and ethyl methyl carbonate, wherein ethylene carbonate has an ultra-high dielectric constant, which can greatly reduce the solubility of metal phosphides (such as ferrous phosphide Fe2P) in the electrolyte, thereby effectively solving the problem of the reduction reaction of the metal phosphide itself when it is dissolved in the electrolyte after long-term circulation and the catalytic reaction of the electrolyte when it is deposited on the negative electrode.
[0037] In addition, the non-free electrolyte is close to the lithium iron phosphate composite material, which is closely related to the dissolution of metal phosphides in the lithium iron phosphate composite material and the formation of repaired SEI film and CEI film. Improving a1 / b1 can effectively inhibit the dissolution of metal phosphides and is conducive to the initial formation of SEI layer and CEI layer with high conductivity and electrochemical stability. The inventors found that the design value of a1 / b1 is sensitive to the change of c. When 0.02c+1≤a1 / b1≤0.22c+1.15 is satisfied, the high-power cycle performance of the battery can be significantly improved. If a1 / b1 is less than 0.02c+1, the positive electrode material will suffer from serious metal phosphide dissolution from the positive electrode into the electrolyte; if a1 / b1 is greater than 0.22c+1.15, the ethylene carbonate enriched in the pores of the positive electrode material will suffer from severe oxidation and decomposition reaction, resulting in the lithium iron phosphate LiFePO4 and the metal phosphide being covered with a large amount of organic products that hinder electron transmission, causing the metal phosphide to be unable to exert its effect. At the same time, the formation of an excessively thick CEI layer also reduces the reversible capacity of LiFePO4.
[0038] In the embodiment of the present application, the non-free electrolyte and the free electrolyte in the battery are designed differently. The non-free electrolyte includes the electrolyte in the pores of the positive electrode plate, the electrolyte in the pores of the negative electrode plate, and the electrolyte in the pores of the diaphragm. It is in direct contact with the electrode and the diaphragm, dominates the formation and repair process of the SEI film, participates in the lithium ion desolvation effect, and directly determines the SEI film impedance R in the battery. SEI and charge transfer resistance R ct ; The free electrolyte exists in the battery cavity outside the material pores, and there is no absolute physical barrier between it and the non-free electrolyte. When the non-free electrolyte is insufficiently consumed, the free electrolyte is automatically absorbed as a supplement through the capillary action of the pole piece and the diaphragm. When the content of a certain component in the non-free electrolyte is higher than that of the free electrolyte, the content of the component decreases after the non-free electrolyte absorbs the free electrolyte; when the content of a certain component in the non-free electrolyte is lower than that of the free electrolyte, the content of the component increases after the non-free electrolyte absorbs the free electrolyte. There are dynamic differences in the electrolyte composition of the two regions during the cycle consumption process, so the component content of the battery during use also changes dynamically.
[0039] According to some specific embodiments of the present application, 0.001≤c≤3 is satisfied, and thus, introducing a suitable amount of metal phosphide into the lithium iron phosphate composite material can further effectively improve the conductivity of the positive electrode sheet, thereby further effectively reducing the high-power cycle polarization of the battery and further improving the retention rate of the reversible capacity. The inventors have found that if its content is too low, it will not be able to reduce polarization; if its content is too high, it will cause a large amount of decomposition of the electrolyte.
[0040] According to some further specific embodiments of the present application, the metal phosphide includes at least one of ferrous phosphide and ferric phosphide. Introducing the above-mentioned types of metal phosphides into the lithium iron phosphate composite material can effectively improve the conductivity of the positive electrode plate, thereby effectively reducing the high-power cycle polarization of the battery and improving the retention rate of the reversible capacity.
[0041] According to some specific embodiments of the present application, 1<a1 / b1<1.5 is satisfied. EC has an ultra-high dielectric constant, which can greatly reduce the solubility of metal phosphides; and EC dominates the first solvation shell, and Li + The formed solvent clusters have higher LUMO values than other solvent clusters and better reduction resistance. Therefore, the EC in the non-free electrolyte (i.e., the localized electrolyte closest to the active material) is limited to be higher than the EMC (i.e., 1 < a1 / b1). However, when the EC content is too much higher than the EMC content, it means that EC will also be enriched in the pores of the positive electrode active material and accelerate the oxidation of the electrolyte, which will lead to rapid decay of battery energy during the cycle. Therefore, the upper limit of a1 / b1 is designed (a1 / b1 < 1.5).
[0042] According to some other specific embodiments of the present application, the free electrolyte includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC), the mass proportion of ethylene carbonate (EC) in the free electrolyte is a2, and the mass proportion of ethyl methyl carbonate (EMC) in the free electrolyte is b2, satisfying 0.5<a2 / b2<1. EMC dominates the second solvation shell, and is more balanced in LUMO and HOMO values compared to other linear carbonates such as DMC and DEC, which is conducive to the widening of the electrochemical window of the electrolyte, and can reduce the polarization of transmission and reaction on the positive and negative electrodes. Therefore, the present application defines that the EMC in the free electrolyte (i.e., the localized electrolyte for building the transmission reaction channel) is higher than EC (i.e., a2 / b2<1). However, when EMC is much higher than EC, the Fe2P dissolved in the free electrolyte will diffuse rapidly and be reduced and deposited on the negative electrode, accelerating the consumption of the electrolyte. This will also lead to rapid attenuation of battery energy during the cycle, and even a sudden deterioration of the cycle due to insufficient interface protection and electrolyte surplus. Therefore, the lower limit of a2 / b2 is designed (0.5<a2 / b2).
[0043] According to some other specific embodiments of the present application, a2<a1 is satisfied, thereby further ensuring that the EC in the non-free electrolyte for reaction generation and repair of the SEI film is sufficient, and a low-impedance SEI repair layer can be quickly generated; at the same time, it can further ensure that the EC in the free electrolyte for lithium salt dissociation is sufficient, and has a relatively stable electrochemical window, reducing the dissolution behavior of iron phosphide.
[0044] According to some other specific embodiments of the present application, 35%≤a1+b1≤75% and 35%≤a2+b2≤75% are satisfied, thereby ensuring high polarity and high electrochemical stability of the electrolyte.
[0045] In the embodiment of the present application, the battery is a lithium-ion battery. Specifically:
[0046] The positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on the surface of at least one side of the positive electrode collector, the positive electrode active material layer includes a lithium iron phosphate composite material, the lithium iron phosphate composite material includes lithium iron phosphate particles and metal phosphide attached to at least a portion of the surface of the lithium iron phosphate particles, the ratio of the mass of the metal phosphide to the mass of the lithium iron phosphate particles is c, satisfying 0.02c+1≤a1 / b1≤0.22c+1.15.
[0047] In some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0048] In some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0049] In some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinyl ether, polymethyl methacrylate (PMMA), polyhexafluoropropylene, and styrene-butadiene rubber (SBR).
[0050] In some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet (such as positive electrode active material, conductive agent, binder) are dispersed in an organic solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0051] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0052] In some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0053] In some embodiments of the present application, the negative electrode active material may be a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, etc. The silicon-based material may include at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin-oxygen compounds, and tin alloys.
[0054] In some embodiments of the present application, the negative electrode active material layer may further optionally include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0055] In some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0056] In some embodiments of the present application, the negative electrode active material layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na) and the like.
[0057] In some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet (such as negative electrode active material, conductive agent, binder and any other components) are dispersed in an organic solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0058] The second aspect of the present application proposes a method for injecting liquid in a battery of one or more embodiments. According to the embodiments of the present application, the above-mentioned injection method includes: using one injection of electrolyte for the first injection, standing, and forming; using two injections of electrolyte for the second injection, high temperature aging, and capacity separation.
[0059] Specifically, the above-mentioned injection method includes:
[0060] S100: Use one injection of electrolyte for the first injection, let it stand, and form;
[0061] In this step, an electrolyte is injected for the first time, left to stand, and formed to form an initial SEI film on the surface of the positive electrode active material and the negative electrode active material respectively. The part of the electrolyte remaining in the positive electrode plate, the negative electrode plate and the pores of the diaphragm after the electrolyte formation reaction forms a non-free electrolyte in the initial state.
[0062] S200: Use two injections of electrolyte for the second injection, high temperature aging, and volume separation.
[0063] In this step, two injections of electrolyte are used for the second injection, high temperature aging, and volume separation to form the initial state of free electrolyte. When one injection of electrolyte is excessive, the part that is not consumed or does not enter the pores of the diaphragm, positive electrode sheet, and negative electrode sheet merges with the second injection of electrolyte to form the initial state of free electrolyte, which is used to supplement the ion channels required for long circulation.
[0064] According to the injection method of the embodiment of the present application, the electrolyte required for the battery formation stage and the electrolyte required for the circulation stage are separated by secondary injection, and the local distribution characteristics of the non-free electrolyte and the free electrolyte in the initial state of the battery are flexibly controlled. The dissolution of metal phosphides can be effectively inhibited and it is beneficial to the initial formation of SEI layer and CEI layer with high conductivity and electrochemical stability, thereby achieving the effect of improving the high-power cycle energy retention rate, and at the same time ensuring the high polarity and high electrochemical stability of the electrolyte.
[0065] According to some specific embodiments of the present application, a shot of electrolyte includes ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in a shot of electrolyte is M1, and the mass proportion of ethyl methyl carbonate in a shot of electrolyte is N1, satisfying: 1≤M1 / N1≤0.4c+1.7. By limiting 1≤M1 / N1≤0.4c+1.7, the dissolution of Fe2P can be effectively inhibited, and the CEI film can be effectively formed and repaired. The inventors found that if M1 / N1 is too low, it is not enough to inhibit the dissolution and deposition of Fe2P, which deteriorates the cyclic reversible capacity; if M1 / N1 is too high, the benefit of Fe2P in reducing polarization is eliminated, which will also cause the deterioration of the cyclic reversible capacity.
[0066] According to some further specific embodiments of the present application, 10%≤N1≤M1≤35% is satisfied, thereby further effectively inhibiting the dissolution of Fe2P and effectively forming and repairing the CEI film.
[0067] According to some other specific embodiments of the present application, the two injections of electrolyte include ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the two injections of electrolyte is M2, and the mass proportion of ethyl methyl carbonate in the two injections of electrolyte is N2, satisfying: 15%≤M2≤N2≤55%, thereby further ensuring the high polarity and high electrochemical stability of the electrolyte.
[0068] In the embodiments of the present application, the electrolyte demand of the battery is related to the cell capacity, and the electrolyte demand can be represented by the injection coefficient (injection amount / cell capacity). According to some specific embodiments of the present application, the injection coefficient of the sum of one injection of electrolyte and two injections of electrolyte is 2.5g / Ah to 5g / Ah, and as an example, it can be 2.5g / Ah, 3g / Ah, 3.5g / Ah, 4g / Ah, 4.5g / Ah, 5g / Ah, etc. By limiting the injection coefficient to the above range, it can ensure that the diaphragm and the positive and negative pole pieces are fully infiltrated, and the electrolyte will not swell or accumulate at the bottom of the battery due to excessive amount of electrolyte, causing local lithium precipitation. 3.5g / Ah to 4.5g / Ah is preferred.
[0069] According to some further specific embodiments of the present application, the mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2). By limiting the mass ratio of the first injection of electrolyte to the second injection of electrolyte within the above range, it can be ensured that the SEI protective layer formed by chemical formation is uniform, and at the same time, the effect of high-power cycling can be effectively improved.
[0070] The third aspect of the present application proposes an energy storage device. According to an embodiment of the present application, the above energy storage device includes a battery of the above embodiment or a battery obtained by the injection method of the above embodiment. As a result, the energy storage device has excellent high-power cycle performance. It should be noted that the above-described features and advantages for the battery are also applicable to the energy storage device and will not be repeated here.
[0071] Specifically, the energy storage device of the present application may include but is not limited to a battery module, a battery pack, a battery system, etc. In addition, the energy storage device of the present application may also include at least one of an electric energy storage device for the power generation side of the power system, an electric energy storage device for the power distribution side of the power system (such as an electrochemical energy storage device), and an electric energy storage device for the user side of the power system.
[0072] The fourth aspect of the present application proposes an electric power system. According to an embodiment of the present application, the electric power system includes: electric equipment, and an energy storage device as in the above embodiment, and the energy storage device supplies power to the electric equipment. As a result, the electric power system has excellent high-power cycle performance. It should be noted that the above-described features and advantages for the battery are also applicable to the electric power system and will not be repeated here.
[0073] The above-mentioned power consumption system may include but is not limited to mobile phones, tablet computers, laptop computers, desktop computers, smart bracelets, smart watches, e-readers, game consoles and other portable electronic devices. It may also include but is not limited to vehicles such as cars, trucks, cars, vans, motor vehicles, high-speed trains, electric vehicles, etc. In addition, it may also be various household appliances, such as but not limited to refrigerators, electric lights, air conditioners, etc.
[0074] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0075] Example 1
[0076] This embodiment provides a lithium ion battery, and the preparation method thereof includes:
[0077] 1) Preparation of positive electrode sheet:
[0078] The initial lithium iron phosphate (LiFePO4) active material obtained by calcination was purchased from the market (maximum calcination temperature 790°C, inert gas), and the mass content of ferrous phosphide (Fe2P) in the initial lithium iron phosphate active material was tested to be about 3.1%. The magnetic impurity removal method was adopted, and the phase content gradient of Fe2P in the active material was set in sequence according to the requirements of each embodiment (as shown in Table 1), and lithium iron phosphate composite materials with different contents of Fe2P were obtained by magnetic separation. The magnetic separation process is as follows: The initial lithium iron phosphate active material is dispersed in ethanol by ultrasonic dispersion method. Then a magnetic bar with a magnetic induction intensity of 6000g is added to the dispersion, and mechanical stirring is carried out at medium speed for a period of time. Subsequently, the magnetic bar is taken out and the remaining dispersion is dried to obtain LiFePO4 with different Fe2P phase contents.
[0079] The obtained lithium iron phosphate composite material containing a specific content of Fe2P, conductive carbon black (SP), and adhesive polyvinylidene fluoride (PVDF) were dispersed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 97:2.5:0.5 and mixed evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on the positive electrode current collector aluminum foil. The coating weight per unit area of the positive electrode slurry was 33 mg / cm 2 After embossing, drying, cold pressing, slitting and cutting, the positive electrode sheet is obtained.
[0080] 2) Preparation of negative electrode sheet:
[0081] The negative electrode active material artificial graphite, conductive carbon black (SP), thickener (CMC) and binder (SBR) were dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry was coated on the negative electrode current collector copper foil. The coating weight per unit area of the negative electrode slurry was 16 mg / cm 2 After drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained.
[0082] 3) Preparation of electrolyte:
[0083] In an argon atmosphere glove box with a moisture and oxygen content of ≤0.1ppm, the solvents EC and EMC were mixed according to the designed mass proportions in Table 1, supplemented with 12% lithium hexafluorophosphate, 2.5% vinylene carbonate, and 0.5% vinyl sulfate, and the remaining part was supplemented with DMC, and stirred until completely dissolved. The types and mass proportions of lithium salts and additive components in one shot and two shots of electrolyte were designed without difference.
[0084] 4) Preparation of isolation membrane:
[0085] A 16 μm polyethylene film was used.
[0086] 5) Battery assembly:
[0087] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to separate the positive and negative electrode sheets, and then wound into a bare battery cell. After welding the pole ears, the battery cell is assembled into an outer package, and vacuum dried after hot pressing, and then a secondary liquid injection process is performed. Specifically, the first injection of electrolyte is performed, and the battery cell is packaged, left to stand, and formed; the second injection of electrolyte is performed, and the battery cell is left to stand at high temperature, and the capacity is tested, etc., and finally a soft-pack lithium-ion battery with a capacity of 3.2Ah is prepared.
[0088] The formation process adopts the following process: Step 1: the battery cell is allowed to stand in a 45°C formation cabinet for 10 minutes, and charged at a rate of 0.1C for 7 minutes to 1.17% SOC; Step 2: Stand for 3 minutes, and charge at a rate of 0.2C to 30% SOC.
[0089] Example 1-2 to Example 1-34
[0090] The preparation methods of Examples 1-2 to 1-34 are basically the same as those of Example 1, and the differences are detailed in Table 1.
[0091] Comparative Example 1-1
[0092] The preparation method of this comparative example is basically the same as that of Example 1, except that:
[0093] Comparative Example 1-1 uses a one-time liquid injection process, and the preparation method is as follows: injecting electrolyte, packaging the battery cell, standing, forming, high-temperature standing, capacity testing, etc., and finally preparing a soft-pack lithium-ion battery with a capacity of 3.2Ah; wherein the formation process and standing conditions are consistent with Example 1.
[0094] Comparative Example 1-2 to Comparative Example 1-3
[0095] The preparation methods of Comparative Examples 1-2 to 1-3 are basically the same as those of Example 1, and the differences are detailed in Table 1.
[0096] In Table 1, the injection coefficient of each embodiment and comparative example is fixed at 4.0 g / Ah; the mass ratio of the first injection of electrolyte and the second injection of electrolyte of each embodiment and comparative example is fixed at 7:3; the standing condition after the first injection is 45±5°C for 24 hours, and the formation temperature is 45°C; the high temperature aging condition after the second injection is 45±5°C for 24 hours.
[0097] Example 2-1 to Example 2-11
[0098] The electrolyte and positive electrode designs of Examples 2-1 to 2-10 are consistent with those of Example 1-4, and the electrolyte and positive electrode designs of Example 2-11 are consistent with those of Example 1-32, and the differences are detailed in Table 2. In Table 2, the injection coefficient, the ratio of the first injection and the second injection are specifically listed; the temperature and time parameters in the second injection are consistent with those in Table 1.
[0099] The lithium-ion batteries of Examples 1-1 to 1-34 and Comparative Examples 1-1 to 1-3 were respectively subjected to free electrolyte composition test, non-free (pore) electrolyte composition test and 1P high-power cycle performance test. The results are shown in Table 1.
[0100] The lithium-ion batteries of Examples 2-1 to 2-11 were respectively subjected to free-state electrolyte composition test, non-free-state (pore) electrolyte composition test and 1P high-power cycle performance test. The results are shown in Table 2.
[0101] Determination of Fe2P content in lithium iron phosphate composite materials:
[0102] Quantitative analysis: X-ray diffraction was used to analyze the phase composition, phase abundance, unit cell parameters, and crystallinity of the lithium iron phosphate composite material. The radiation source was CuKα, and the data was collected by step scanning with a step length of 0.02° (2θ angle). The counting time for each step was 1s. The results of the product were Rietveld refined to obtain the unit cell parameters of the lithium iron phosphate composite material, the phase composition and phase content of the product. LiFePO4 standard card (JCPDS Card No.40-1499: ), Fe2P (2θ=40.2°), refinement accuracy Rw / Rexp<3%, Rw<2~5%Rwp, Rw weighted pattern variance factor, Rexp expected variance factor.
[0103] Qualitative characterization: The surface morphology of lithium iron phosphate composite material particles was observed by transmission electron microscopy (TEM) under magnification of a local area. The lattice fringe plane spacing of LiFePO4 in the electron diffraction (SAED) diagram of the selected sample area was 0.34nm, corresponding to the (111) crystal plane, and had single crystal characteristics. In addition, the crystal phase of the conductive phase Fe2P can be found in the surface layer of the LiFePO4 particles, and the lattice fringe spacing of 0.22nm and 0.19nm correspond to the (111) and (210) crystal planes, respectively.
[0104] All experiments were performed at room temperature.
[0105] Free electrolyte composition test:
[0106] Discharge the battery with outer packaging with a current of 0.05C to 0% SOC (2.0V), cut a notch of about 0.5cm on the right side facing the positive column of the battery, and cut the same notch on the right side facing the negative column, ensuring that the two notches are on the diagonal line, and pour the free electrolyte into the fluoride bottle from the small opening on the side of the positive column until intermittent dripping flows down and count for 30s.
[0107] Gas chromatography-mass spectrometry (GC-MS) was used to test the types and relative mass contents of organic components in the collected electrolyte.
[0108] Non-free (pore) electrolyte composition test:
[0109] Remove the outer packaging, take out a single bare cell, quickly peel off the electrode, put it into an aluminum-plastic bag, add enough acetonitrile solvent to completely immerse the electrode, seal the aluminum-plastic bag containing acetonitrile solvent and electrode, and let it stand at 35±10℃ for 3 days.
[0110] Gas chromatography-mass spectrometry (GC-MS) was used to test the types and relative mass contents of organic components in the collected electrolyte.
[0111] 1P high power cycle performance test:
[0112] Charge to 3.65V at 45℃ with 1P constant power, then discharge to 2.5V with 1P constant power. The energy of charge and discharge in the Xth cycle is recorded as CE x ,DE x , until X = 1000. The battery cycle life is evaluated by the energy retention rate η after the cycle, η = DE 1000 / DE3.
[0113] Table 1
[0114]
[0115]
[0116] Table 1 continued
[0117]
[0118]
[0119] Note: The optimized relationship between c and a1 / b1 is 0.02c+1≤a1 / b1≤0.22c+1.15, “Y” means that the above formula is satisfied, and “N” means that the above formula is not satisfied.
[0120] Table 2
[0121]
[0122]
[0123] Table 1 and Table 1 continuation evaluate the relationship between the design parameters of the iron phosphide-containing positive electrode and the localized electrolyte and the 45°C 1P cycle energy retention rate. It can be seen from Table 1 and Table 1 continuation that the 45°C 1P cycle energy retention rates of the embodiments and comparative examples that do not meet 0.02c+1≤a1 / b1≤0.22c+1.15 are poor, while the 45°C 1P cycle energy retention rates of the embodiments that meet 0.02c+1≤a1 / b1≤0.22c+1.15 are relatively excellent.
[0124] It can be seen from Comparative Example 1-1 that the conventional method of using a single injection and thoroughly removing the iron phosphide in the positive electrode until it cannot be detected has a 45°C 1P high-power cycle energy retention rate of only 70%. It can be seen from Comparative Example 1-2 that the use of a secondary injection and the retention of a certain amount of iron phosphide in the positive electrode, but the design parameters of the secondary injection electrolyte are not met, and the cycle energy retention rate is not only not improved but seriously deteriorated. This is because the lack of EC and EMC key solvents in the single injection electrolyte, only lithium salts, additives and DMC solvents are used, which are not enough to build an initial stable SEI protective layer, and energy diving occurs during the cycle. It can be seen from Comparative Examples 1-3 that the use of a secondary injection and the retention of a certain amount of iron phosphide in the positive electrode, but the design parameters of the relationship between the electrolyte components and the positive electrode iron phosphide content of the present application are not met, and the cycle is also deteriorated. This is because the electrolyte cannot form a localized concentration difference as required, and the iron phosphide is easily dissolved in the electrolyte and deposited on the negative electrode, catalyzing the reduction and decomposition of the electrolyte, but seriously deteriorating the battery cycle performance.
[0125] It can be seen from Examples 1-1 to 1-34 that by adjusting the contents of EC and EMC in the first and second electrolyte injections, the localized distribution characteristics of EC and EMC in the electrolyte can be obtained, and when the design parameters satisfy 1<a1 / b1<1.5, 0.5<a2 / b2<1, and a2<a1, the 45℃1P cycle energy retention rate is improved to varying degrees. When the localized distribution of EC and EMC in the electrolyte is designed in combination with a positive electrode containing iron phosphide, when the parameters satisfy 0.02c+1≤a1 / b1≤0.22c+1.15, the high-power cycle energy retention rate of 45℃1P can be greatly improved. Among them, Example 1-1 completely removes impurities from the iron phosphide in the positive electrode until it is undetectable. Only by optimizing the usage of EC and EMC in the secondary injection, the effect of improving the cycle has been achieved compared with the comparative example. In Examples 1-2 to 1-9, higher contents of iron phosphide are retained successively, and the electrolyte injection method and electrolyte formula remain unchanged. The cycle improvement amplitude first increases and then decreases, which indicates that the phase content c of Fe2P in the positive electrode active material has an upper and lower range of 0.001%≤c≤3%. If it is lower than the lower limit, the effect of reducing polarization cannot be achieved, and if it is higher than the upper limit, a large amount of electrolyte decomposition is caused.
[0126] It can be seen from Examples 1-10 to 1-30 that the amount of EC and EMC added to one injection of electrolyte has a great influence on the non-free electrolyte and will also indirectly affect the free electrolyte. This is because one injection is mainly used to form the initial SEI layer. When there is a surplus of one injection of electrolyte after formation, it will be distributed in different areas of the battery in the form of non-free and free states. After the second injection is completed, the newly injected electrolyte quickly mixes with the remaining free state part of the first injection to form a free electrolyte together, which is used to supplement the ion channels required for long circulation.
[0127] In Examples 1-10 and 1-11, a large amount of EC is added (i.e., M1 is large), and in Examples 1-15 and 1-16, a small amount of EMC is added (i.e., N1 is small), which means that EC in the non-free electrolyte and the free electrolyte is too much higher than EMC, causing EC to be enriched in the pores of the positive electrode active material and accelerating the oxidation of the electrolyte, which will lead to rapid decay of battery energy during the cycle. In Examples 1-13 and 1-14, a small amount of EC is added (i.e., M1 is small), and in Example 1-19, a large amount of EMC is added (i.e., N1 is large), which means that EMC in the non-free electrolyte is too much higher than EC, causing EC to fail to dominate the first solvation shell, poor electrolyte reduction stability in the pores, lack of SEI repair function, and therefore unsatisfactory cycling. Based on Examples 1-11 and 1-13, the iron phosphide content in the positive electrode and the amount of EC and EMC added in one injection were adjusted, i.e., Examples 1-21 and 1-20, so that both the non-free electrolyte and the free electrolyte satisfied the design relationship, and it was found that the cycle was significantly improved.
[0128] The high M2 / N2 in Examples 1-22 and 1-29, the small M2 value in Example 1-26, and the large N2 value in Example 1-27 will also cause the EC and EMC distribution in the non-free electrolyte and the free electrolyte to be outside the optimized range. Summarizing a large number of experiments, the iron phosphide content in the positive electrode and the amount of EC and EMC added in the first and second electrolyte injections can be corrected according to the design optimization range, and the obtained Examples 1-31 to 1-34 can significantly improve the cycle performance compared with Comparative Example 1-1. Among them, the 45°C 1P high-power cycle energy retention rate of Example 1-32 is the highest, reaching 87%.
[0129] Table 2 evaluates the effects of the secondary electrolyte injection coefficient and injection mass ratio on the distribution of EC and EMC in the free electrolyte and non-free electrolyte, as well as the impact on the high-power cycling performance.
[0130] As can be seen from Table 2, the injection mass ratio of Example 2-1 is too low, the diaphragm and the electrode cannot be fully infiltrated, resulting in a partial lack of film protection for the electrode that did not enter the electrolyte during the formation stage, resulting in a low 45°C 1P high-power cycle energy retention rate; Example 2-6 has excessive electrolyte swelling due to excessive amount of electrolyte, and redundant electrolyte will accumulate at the bottom of the battery to cause lithium precipitation, resulting in a low 45°C 1P high-power cycle energy retention rate, so the injection coefficient of the sum of the first injection electrolyte and the second injection electrolyte is limited to 2.5-5g / Ah, among which the injection coefficient is preferably 3.5-4.5g / Ah. In Example 2-7, since the ratio of the first and second injection volumes is too low, i.e., less than 6:4, the injection volume in the first injection is insufficient for sufficient infiltration, and the SEI protective layer obtained by formation is uneven. After the second injection, the area where SEI is not formed and the electrolyte are electronically conductive, resulting in the decomposition and accumulation of electrolyte byproducts, which leads to a low 45°C 1P high-power cycle energy retention rate; in Example 2-10, since the ratio of the first and second injection volumes is too high, i.e., greater than 8:2, the proportion of the second injection is low, and the free electrolyte components mainly come from the electrolyte components that have not been consumed in the first injection, which are basically the same as the non-free electrolyte components. Under such a ratio, the relationship between the positive electrode iron phosphide content and a1 / a2 cannot meet the optimization range, and the cycle improvement is weak. Therefore, the electrolyte mass ratio of the first injection and the second injection is limited to 6:4 to 8:2.
[0131] In Example 2-11, after finely adjusting the injection coefficient and the secondary injection mass ratio on the basis of Example 1-32, the high-power cycle energy retention rate of 45°C 1P is further improved, reaching a maximum of 90%.
[0132] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0133] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the electrolyte comprises a free electrolyte and a non-free electrolyte, and the non-free electrolyte comprises an electrolyte in the pores of the positive electrode sheet, an electrolyte in the pores of the negative electrode sheet and an electrolyte in the pores of the separator; The non-free electrolyte includes ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the non-free electrolyte is a1, and the mass proportion of ethyl methyl carbonate in the non-free electrolyte is b1; The positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes a lithium iron phosphate composite material, the lithium iron phosphate composite material includes lithium iron phosphate particles and metal phosphide attached to at least a portion of the surface of the lithium iron phosphate particles, the mass content of the metal phosphide in the lithium iron phosphate composite material is c%, and 0.02c+1≤a1 / b1≤0.22c+1.15 is satisfied.
2. The battery according to claim 1, characterized in that Satisfies 1<a1 / b1<1.5; And / or, 35%≤a1+b1≤75% is satisfied.
3. The battery according to claim 1, characterized in that Satisfies 0.001≤c≤3.
4. The battery according to claim 1, characterized in that The metal phosphide includes at least one of ferrous phosphide and ferric phosphide.
5. The battery according to any one of claims 1 to 4, characterized in that The free electrolyte includes ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the free electrolyte is a2, the mass proportion of ethyl methyl carbonate in the free electrolyte is b2, and 0.5<a2 / b2<1 is satisfied; And / or, 35%≤a2+b2≤75% is satisfied.
6. The battery according to claim 5, characterized in that Satisfies a2<a1.
7. A method for injecting liquid into a battery as claimed in any one of claims 1 to 6, characterized in that: include: Use one injection of electrolyte for the first injection, let it stand, and form; Use two injections of electrolyte for the second injection, high temperature aging, and volume separation.
8. The liquid injection method according to claim 7, characterized in that: The one injection of electrolyte includes ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the one injection of electrolyte is M1, the mass proportion of ethyl methyl carbonate in the one injection of electrolyte is N1, and the following is satisfied: 1≤M1 / N1≤0.4c+1.
7.
9. The liquid injection method according to claim 8, characterized in that: Satisfies 10%≤N1≤M1≤35%.
10. The liquid injection method according to claim 7, characterized in that: The two electrolytes include ethylene carbonate and ethyl methyl carbonate, the mass proportion of ethylene carbonate in the two electrolytes is M2, and the mass proportion of ethyl methyl carbonate in the two electrolytes is N2, satisfying: 15%≤M2≤N2≤55%.
11. The liquid injection method according to any one of claims 7 to 10, characterized in that: The mass ratio of the first injection of electrolyte to the second injection of electrolyte is (6:4) to (8:2).
12. The liquid injection method according to any one of claims 7 to 10, characterized in that: The total injection coefficient of the first injection of electrolyte and the second injection of electrolyte is 2.5 g / Ah to 5 g / Ah.
13. An energy storage device, characterized in that: A battery comprising the battery according to any one of claims 1 to 6 or a battery obtained by the injection method according to any one of claims 7 to 12.
14. An electricity system, characterized in that: include: Electrical equipment, and The energy storage device as claimed in claim 13, wherein the energy storage device supplies power to the electrical equipment.